ANALISIS TERHADAP PERLINDUNGAN HUKUM PENGGUNA JASA TRANSPORTASI ONLINE ATAS PERBUATAN TIDAK MENYENANGKAN OLEH PENGEMUDI OJEK ONLINE MELALUI MEDIA SOSIAL MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Belinda Selfira; Jeane Neltje (Jurnal Hukum Adigama, 2021)
Information and communication technology has changed the behavior and lifestyle of people globally. The development of information and communication technology has caused the world to become borderless, where one person can access and send information to others quickly over long distances. Based on the contents in this thesis, there are problems. First, how is the responsibility of Go-Jek business actors in terms of unpleasant acts committed by motorbike taxi drivers or motorbike taxi drivers to consumers who use Go-Jek services, secondly, what are the obstacles to Go-Jek business actors in terms of unpleasant acts committed by drivers? or drivers to consumers who use Go-Jek services, then the purpose of the research in this thesis is the first to find out GoJek's responsibilities in terms of unpleasant acts committed by Go-Jek drivers to consumers who use Go-Jek services, the second is to find out Go-Jek's obstacles in terms of inappropriate actions. fun that is done by gojek drivers to consumers who use gojek services. Based on the research data as follows: many occur and often encountered are vehicles registered in online applications are different from vehicles used by drivers or online transportation drivers, and the conclusions in the research data are as follows: Related to sanctions that have been agreed upon that sanctions are case by case, from the Gojek side, it is necessary to know the details of the incident thoroughly from both parties so that appropriate sanctions can be given or not.